Proceedings of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290605.3300274
|View full text |Cite
|
Sign up to set email alerts
|

Smart and Fermented Cities

Abstract: What makes a city meaningful to its residents? What attracts people to live in a city and to care for it? Today, we might see such questions as concerns for HCI, given the emerging agendas of smart and connected cities, IoT, and ubiquitous computing: city residents' perceptions of and attitudes towards smart city technologies will play a role in technology acceptance. Theories of "placemaking" from humanist geography and urban planning address themselves to such concerns, and they have been taken up in HCI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 39 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The second key theme found is sense of place, in that individuals spend time living and emotionally interacting with space beyond being physically in it (Abdel-Aziz et al, 2016;Birnbaum et al, 2021;Freeman et al, 2019). Scholars understand it as one of the objectives of placemaking (Chen et al, 2022;Fredericks et al, 2018;Rutha and Abbas, 2021), and it is usually presented as linked to place attachment (Birnbaum et al, 2021;Freeman et al, 2019;Kale, 2019;Polson, 2015;Rutha and Abbas, 2021;Toomey et al, 2021) and identity (Agyekum and Table 5 (continued ) placemaking can be understood as a process on digital communities involving an organic interaction among the digital placemakers as they participate towards a common cause of sustaining the local culture of geographic spaces while engaging through the key strategies towards the process Stokes et al (2018) No Markusen and Gadwa, (2010) Creative placemaking…”
Section: Yes Digital Placemakingmentioning
confidence: 99%
See 1 more Smart Citation
“…The second key theme found is sense of place, in that individuals spend time living and emotionally interacting with space beyond being physically in it (Abdel-Aziz et al, 2016;Birnbaum et al, 2021;Freeman et al, 2019). Scholars understand it as one of the objectives of placemaking (Chen et al, 2022;Fredericks et al, 2018;Rutha and Abbas, 2021), and it is usually presented as linked to place attachment (Birnbaum et al, 2021;Freeman et al, 2019;Kale, 2019;Polson, 2015;Rutha and Abbas, 2021;Toomey et al, 2021) and identity (Agyekum and Table 5 (continued ) placemaking can be understood as a process on digital communities involving an organic interaction among the digital placemakers as they participate towards a common cause of sustaining the local culture of geographic spaces while engaging through the key strategies towards the process Stokes et al (2018) No Markusen and Gadwa, (2010) Creative placemaking…”
Section: Yes Digital Placemakingmentioning
confidence: 99%
“…A third key theme was community engagement. Defined as a process of involving people to collaborate in decisions and outcomes to benefit their communities (Clarke, 2021;Foth, 2017b;Fredericks et al, 2018;Freeman et al, 2019), it is also described to empower communities (Fisher et al, 2018) and improve social cohesion among members (Najafi et al, 2021). It includes community participation (Alvarez et al, 2017;Courage, 2021;Harner et al, 2017;Toland et al, 2020;Witteborn, 2021;Zhang and Gong, 2021), and citizen engagement (Basaraba, 2021;Paraschivoiu and Layer-Wagner, 2021).…”
Section: Mobile Media In Placemakingmentioning
confidence: 99%
“…To support this project of making fundamental change in our eld, we chose to examine a number of cases from eldwork conducted by part of the research team, in which the whole team found phenomena that seemed to embody many of the practical, intellectual, and ideological values with which we were engaging. The cases were drawn from ethnographic eldwork conducted in Taiwan by two of the authors, who have been researching innovation there since 2011, documented in [7,8,36,37,70,71,73]. In the context of this essay, we foreground ethnographic eld research conducted in 2017 and 2018 in one farming village in rural Taiwan.…”
Section: Advancing Theory Using Ethnographymentioning
confidence: 99%
“…A similar investigation by McMillan et al explores how data is used in governance in a number of Northern European cities; however, they focus on applications that involve citizens as data collectors or consumers, rather than urban sensor networks [33]. Others have looked at how databases are used across multiple scales of public sector work [30], examined the uptake of data-driven systems by police departments [62], investigated the bottom-up processes used in a local co-design projects in Taipei [21], assessed effects of the regional governance structure in the Boston metropolitan area on opportunities for creating a large-scale smart-city ecosystem [27], surveyed those implementing smart city projects across a number of cities [46], and critiqued the technocratic underpinnings of smart city planning and its capacity to support urban sustainability and ecological objectives [66]. These authors have engaged with the various motivations for developing data-driven infrastructure at a local scale and reflected upon both the power of data and the ways that data is influenced by power dynamics, including those between city residents and governing entities or between local and regional governments.…”
Section: Empirical and Design Investigations Into Smart Citiesmentioning
confidence: 99%
“…Through an investigation of a number of data-driven projects on a single city street, Taylor et al discuss how "small worlds" of data are created due to the boundaries of both physical and social geography [60]. Freeman et al bring the concept of "placemaking" from geography to bear on the design of smart cities, highlighting the importance of understanding the iterative human processes of sense-making involved in creating places [21,49].…”
Section: Empirical and Design Investigations Into Smart Citiesmentioning
confidence: 99%